Design and validation of an instrument to evaluate intrinsic and extrinsic factors of academic performance in medical students. - Domínguez Celis, Gustavo; Mendoza Anaya, Lorena; Reza López , Sandra Alicia; Ishida Gutiérrez, María Cecilia; Fierro Fierro , Omar (Spanish Journal of Medical Education, 2026)
Background: Low academic performance is a significant problem in medical programs that affects students’ academic trajectories and well-being. This phenomenon results from the complex interaction between intrinsic factors (cognitive and emotional) and extrinsic factors (contextual and social). However, there remains a lack of validated instruments that comprehensively assess this multiplicity of factors in the Mexican context. The systematic identification of these factors is essential for designing effective preventive interventions. Objective To design and validate an instrument to systematically identify and assess the intrinsic and extrinsic factors that influence academic performance in medical students. Method: An instrumental study with an exploratory sequential design was conducted. Phase I: literature review in six specialized databases, 57 exploratory interviews with discourse analysis, and preliminary instrument development. Phase II: two pilot tests (n₁=33, n₂=45) and two rounds of expert judgment validation (5 and 6 experts respectively). The Content Validity Coefficient (CVC) was used as a measure of reliability.Results: The first round of validation of the 42 preliminary items obtained a total CVC of 0.902. After incorporating expert recommendations, the final 38-item version achieved a total CVC of 0.974, exceeding international acceptance criteria. The final instrument integrates four dimensions that operationalize the key factors: (1) sociodemographic characteristics and academic background; (2) metacognition and self-regulation; (3) academic emotions and support networks; and (4) sleep habits and mental health. Conclusion: A validated, reliable, and comprehensive instrument was developed that operationalizes the intrinsic factors (metacognition, emotional regulation, mental health) and extrinsic factors (academic background, socioeconomic context, support networks) that determine academic performance in Mexican medical students. This tool facilitates early identification of academic risk and provides a foundation for designing contextualized and personalized educational interventions.